IMPLEMENTASI STRATEGI PENGELOLAAN SDM DAN DIGITAL MARKETING UNTUK KEMAJUAN UMKM HEALTY FOOD PADA CEMILAN PEMALANG DI DESA PEGATUNGAN KELURAHAN MULYOHARJO KABUPATEN PEMALANG - Suciningtyas, Santi; Setyorini, Anis; Wulansari, Nunung; Sofia, Wildatun; Arif, Andi (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the management of MSMEs, ensuring their competitiveness and high economic value through various efforts tailored to the demands of the digital era. Several challenges in the field include suboptimal human resource management, which serves as the primary driver in business planning, implementation, and evaluation. Other challenges are also evident in marketing strategy efforts and the lack of simple bookkeeping practices. The implementation method involves direct mentoring and the provision of relevant literacy. The results of this activity demonstrate an increase in skills and understanding of MSME management efforts related to the importance of task allocation in the business, digital marketing strategies, and simple bookkeeping.